Navigation Based on Distance and Width of Road - Gaharwar, Raina D; Patel, Birajkumar V (International Journal of Computer Sciences and Engineering, 2019)
Nowadays people uses Google Maps (digital Navigator) during travelling to get exact road map with proper direction including distance in km and total time remaining to reach out destination. For this purpose people need to have facility like, inbuilt GPS system in vehicle or cell phone with internet connectivity but there are certain limitations. GPS (Global Positioning System) basically works with satellite. It is used to determine location of user. Navigator (Google Map) always gives shortest path during travelling that is the biggest limitation. Many times travellers face problems with width of road and create traffic problems as well on smaller roads. So, it is suggested that navigator should consider road width and based on findings it should provide alternate shortest route. For that in this paper an algorithm is provided for solving this problem.